Altered inheritance CRISPR and the ethics of human genome editing - Baylis, Françoise, 1961- (Harvard University Press, 2019)
With the advent of CRISPR gene-editing technology, designer babies have become a reality. The author insists that scientists alone cannot decide the terms of this changing era in human evolution. Members of the public, with diverse interests and perspectives, must have a role in determining our future as a species. --